Atualização da distribuição de Aedes albopictus no Brasil (1997-2002) Updating of the distribution of Aedes albopictus in Brazil (1997-2002) - Roseli La Corte dos Santos (Universidade de São Paulo, 2003)
Apresenta-se a atualização da distribuição de Aedes albopictus no Brasil, de 1997 até o ano de 2002, segundo dados do Sistema de informação de Febre Amarela e Dengue da Fundação Nacional de Saúde. Verifica-se a ocorrência da espécie em 20 dos 27 Estados brasileiros. Updating regarding the distribution of Aedes albopictus in Brazil is presented for the period from 1997 to 2002. Data from the yellow fever and dengue information system of the National Health Foundation is utilized. It can be seen that this species is present in 20 of the 27 Brazilian states.